2022
DOI: 10.3233/jpd-223277
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Cerebrospinal Fluid Biomarkers of Inflammation in Parkinson’s Disease

Abstract: Given the clear role of inflammation in the pathogenesis of Parkinson’s disease (PD) and its impact on incidence and phenotypical characteristics, this review provides an overview with focus on inflammatory biofluid markers in blood and cerebrospinal fluid (CSF) in PD patient cohorts. In preparation for clinical trials targeting the immune system, we specifically address the following questions: 1) What evidence do we have for pro-inflammatory profiles in blood and in CSF of sporadic and genetic PD patients? 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 103 publications
1
20
0
Order By: Relevance
“…Previous studies of chemokine and cytokine levels in plasma or CSF have pointed to elevations in several pro-inflammatory molecules, although studies vary in the degree and particular cytokines or chemokines observed [13][14][15][16][17][18][19][20][21][22][23][24][25][26] . In the blood, the most consistent changes have been noted in IL-1β and some studies have also pointed to changes in IL-2, IFN-γ, and TNF-α 26 . Two recent studies have evaluated serum cytokines in early-stage PD subjects 13 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of chemokine and cytokine levels in plasma or CSF have pointed to elevations in several pro-inflammatory molecules, although studies vary in the degree and particular cytokines or chemokines observed [13][14][15][16][17][18][19][20][21][22][23][24][25][26] . In the blood, the most consistent changes have been noted in IL-1β and some studies have also pointed to changes in IL-2, IFN-γ, and TNF-α 26 . Two recent studies have evaluated serum cytokines in early-stage PD subjects 13 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Peptides derived from alpha-synuclein (αsyn), the key protein that aggregates in PD and the primary component of Lewy Bodies, can activate T-cells from PD patients 12 . Pro-inflammatory cytokines and chemokines are elevated in blood and cerebrospinal fluid (CSF) specimens from subjects with PD [13][14][15][16][17][18][19][20][21][22][23][24][25][26] . Brain imaging techniques using ligands against translocator protein 18kd (TSPO) as a marker for neuroinflammation have pointed to increased TSPO signal in PD patients [27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…PD is influenced by many factors including a mix of immunogenetics and the environment, such as infection history. In recent years, increasing evidence suggests an association with autoimmune conditions, with the involvement of the immune system or its aberrant responses in patients and various experimental models [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In this special issue, our authors highlight the latest research breakthroughs on the links between immune activation and neuroinflammation and PD, and discuss the challenges and novel therapeutic strategies targeting the immune system ISSN 1877-7171/$35.00 © 2022 -IOS Press.…”
mentioning
confidence: 99%
“…T cells, neutrophils, monocytes, dendritic cells, and natural killer (NK) cells form the cellular immunity, while humoral immunity involves antibodies and complement proteins. Several clinical studies using blood and cerebrospinal fluid (CSF) from PD patients have suggested involvement of both cellular and humoral immunity with evidence of changes in pro-inflammatory and anti-inflammatory mediators [5]. B lymphocytes (especially regulatory subset) are decreased in PD though the relative temporal changes in peripheral and CSF B cells over time in patients still need to be further evaluated [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation